2016
DOI: 10.7554/elife.17716
|View full text |Cite
|
Sign up to set email alerts
|

The skin is a significant but overlooked anatomical reservoir for vector-borne African trypanosomes

Abstract: The role of mammalian skin in harbouring and transmitting arthropod-borne protozoan parasites has been overlooked for decades as these pathogens have been regarded primarily as blood-dwelling organisms. Intriguingly, infections with low or undetected blood parasites are common, particularly in the case of Human African Trypanosomiasis caused by Trypanosoma brucei gambiense. We hypothesise, therefore, the skin represents an anatomic reservoir of infection. Here we definitively show that substantial quantities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
294
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(309 citation statements)
references
References 40 publications
(50 reference statements)
13
294
0
2
Order By: Relevance
“…When parasites penetrate the brain, they cause neuropsychiatric and sleep abnormalities [1620]. Tropism has recently been described to the skin and testis, which is important for transmission by the tsetse and sexually, respectively [1719,21]. T. brucei parasites were also found in the skin of 0.5% patients screened for Onchocerca microfilaria at the Democratic Republic of Congo, suggesting that undiagnosed individuals may be a previously unknown source of transmission [17].…”
Section: Parasites Find a Home In Adipose Tissuementioning
confidence: 99%
See 3 more Smart Citations
“…When parasites penetrate the brain, they cause neuropsychiatric and sleep abnormalities [1620]. Tropism has recently been described to the skin and testis, which is important for transmission by the tsetse and sexually, respectively [1719,21]. T. brucei parasites were also found in the skin of 0.5% patients screened for Onchocerca microfilaria at the Democratic Republic of Congo, suggesting that undiagnosed individuals may be a previously unknown source of transmission [17].…”
Section: Parasites Find a Home In Adipose Tissuementioning
confidence: 99%
“…recently showed by quantitative PCR that the AT harbors around 10-fold more parasites than the average number found in the blood in chronic stages of the disease [20]. Interestingly, in the two studies describing tropism for the skin, many parasites were found in the vicinity of subcutaneous adipocytes [17,18]. Although it remains to be compared the relative number of parasites in skin, visceral adipose tissue and testis from the same mouse, there is no doubt that the adipose tissue is one of the major parasite reservoirs.…”
Section: Parasites Find a Home In Adipose Tissuementioning
confidence: 99%
See 2 more Smart Citations
“…Trypanosomes in infected hosts migrate to privileged extravascular sites which may be adipose tissues, dermis and subcutis of the skin, where they localize and serve as sources for subsequent recrudescence of active patent infection. [100][101][102] Therapeutic agents need to be capable of reaching tissues with sequestered parasites which are shielded from drug effects and in the event of failure to do so, the infected hosts has to recruit endogenous anti-disease strategies to control the infection or be supported exogenously with anti-disease interventions. Even in untreated cases, an argument is tenable for strategies investing in disease mitigation of the infected hosts.…”
Section: Concluding Perspectivesmentioning
confidence: 99%